2019
DOI: 10.1186/s12886-019-1218-7
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal vascular changes in internal carotid artery stenosis: a retrospective cohort study in Chinese population

Abstract: BackgroundTo evaluate choroidal vascularity index (CVI) in eyes with internal carotid artery (ICA) stenosis using binarization tool in enhanced depth images scanned by spectral domain optical coherence tomography.MethodsA retrospective cohort study was conducted in 142 patients with ICA stenosis, and 20 normal control subjects matched with the age, sex, etc. According to the diagnostic criteria, the participants are divided into a normal control group (20 cases), a mild stenosis group (64 cases), a moderate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 23 publications
(23 reference statements)
1
27
0
Order By: Relevance
“…In concordance with recent findings (Sayin et al 2015; Kang et al 2019; Li et al 2019) we found thinner SFCT in patients with CS compared to that of control subjects (Fig. 1).…”
Section: Discussionsupporting
confidence: 93%
“…In concordance with recent findings (Sayin et al 2015; Kang et al 2019; Li et al 2019) we found thinner SFCT in patients with CS compared to that of control subjects (Fig. 1).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, retinal microvascular abnormalities are considered to reflect the degree of cerebral microvascular disease [7]. Several studies [8][9][10][11] have confirmed that ocular manifestations can reflect the changes of carotid vessels; however, the potential of previously employed examination methods is limited. For example, a risk of allergy to contrast media exists in retinal angiography [12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a risk of allergy to contrast media exists in retinal angiography [12]. Moreover, other methods, such as retinal thickness [11] and fundus photography [10], do not possess adequate accuracy for the observation of tiny blood vessels. Optical coherence tomography angiography (OCTA) is a new technology that provides high-resolution retinal vascular images suitable for direct observation of 5 μm capillaries.…”
Section: Introductionmentioning
confidence: 99%
“…The use of deep learning combined with retinal imaging in the diagnosis of cardiovascular conditions is a relatively new area of research (Table 1 [23][24][25][26][27][28][29][30][31]). In 2007, researchers from Australia, Singapore, and the USA showed that retinopathies obtained from fundus photographs were associated with the presence of any degree of coronary artery calcification (CAC) score > 0, measured by cardiac computed tomography scanning (odds ratio (OR): 1.22; 95% CI: 1.04 -1.43) in a multi-ethnic population without clinical heart disease, after adjustment for multiple variables [23].…”
Section: Retinal Imaging Heart Disease and Deep Learningmentioning
confidence: 99%
“…However, in patients with severe internal carotid artery stenosis, SFCT was significantly lower. Those with severe stenosis also had a lower choroidal vascularity index (CVI), illustrating that CVI may be an indicator of stenotic changes in the internal carotid artery [ 27 ].…”
Section: Heart Eye and Aimentioning
confidence: 99%